Inflation targeting rules and welfare in an asymmetric currency area - Giovanni Lombardo (Deutsche Bundesbank, 2004)
This paper studies the effect on monetary policy of a non-homogeneous degree of competition across the (two) members of a monetary union. In particular, we assess the welfare loss brought about by the use of a simple interest rate rule that does not take into account such structural differences. Our results show that, ceteris paribus, the welfare-maximizing central bank should react more aggressively to the inflation pressure generated by the more competitive economy. We extend the results of Benigno (2003) in two ways. First, we show that, if the degree of competition differs across countries, the optimal rule could involve a larger weight on the more "flexible" country. Second, we allow for a non-unitelastic demand for import. We show that this can alter Benigno's results even under asymmetric degree of competition. Our study suggests that the size of the welfare losses due to the neglect of these asymmetries crucially depends on their actual combination. Furthermore, we show that if information on the true extent of the asymmetries is incomplete, the symmetric rule could outperform the optimal rule.
Keywords: E5; F4; E3; E4; 330; currency area; asymmetries; monetary policy rules; imperfect competition; sticky prices; second-order approximation; Inflation Targeting; Geldpolitik; Währungsunion; Preisrigidität; Wettbewerb; Wohlfahrtseffekt; Theorie